Pengaruh Penggunaan Media Sosial dan Pengetahuan Kewirausahaan terhadap Minat Mahasiswa untuk Berwirausaha Di Bidang Teknologi - Bambang Satrionugroho; Sri Tomo (STMIK Sinar Nusantara, 2020)
Students in College are used social media for their various activities, and they have studied entrepreneurship in class. The purpose of this research was to determine the effect of using social media, and entrepreneurial knowledge on students’ interest in entrepreneurs’ technology, partially and simultaneously. This research was conducted a quantitative study. The population was 550 students with the total sample were 110 students of STMIK Sinar Nusantara in 2017-2019 which has been taken the Entrepreneurship class. In this study, data analysis method was used multiple linear regression analysis technique. The result was showed that the partial and simultaneous of using social media, and entrepreneurship knowledge has significant effect on students’ intention in entrepreneurs at the STMIK Sinar Nusantara Surakarta.Keywords : Social Media, Entrepreneurship Knowledge, Interest in Entrepreneurship